Melatonin Regulates Apoptosis and Autophagy Via ROS-MST1 Pathway in Subarachnoid Hemorrhage - Shi, Ligen; Liang, Feng; Zheng, Jingwei; Zhou, Keren; Chen, Sheng; Yu, Jun; Zhang, Jianmin (Frontiers in Molecular Neuroscience, 2018)
Compelling evidence has indicated that imbalance between apoptosis and autophagy may be involved in subarachnoid hemorrhage (SAH). We aimed to investigate the effects and mechanisms of melatonin in the homeostasis of apoptosis and autophagy. One hundred and forty-eight male Sprague Dawley rats were intraperitoneally injected with melatonin or vehicle 2 hours after SAH induction. Western blotting and an immunofluorescent assay were performed to detect the expression of apoptosis- and autophagy-related proteins. The neuroprotective effect of melatonin attenuating SAH-induced neurological deficit and brain edema may be associated with the suppression of SAH-induced neuronal apoptosis and autophagy. Furthermore, melatonin inhibited the cleavage of mammalian sterile 20-like kinase 1 (MST1) protein by reducing reactive oxygen species (ROS) content. These effects of melatonin on regulating the homeostasis between apoptosis and autophagy could be reversed by an MST1 agonist, chelerythrine, via enhancement of MST1 cleavage. In conclusion, exogenous melatonin alleviates SAH-induced early brain injury (EBI) by suppressing excessive neuronal apoptosis and autophagy. The underlying mechanism may, at least in part, involve the ROS-MST1 pathway.